The Romance of War; or, The Highlanders in Spain, Volume 1 (of 3) - Grant, James, 1822-1887 (Salt Lake City, UT : Project Gutenberg, 2017)
"The Romance of War; or, The Highlanders in Spain, Volume 1 (of 3)" by James Grant is a historical novel written in the mid-19th century. The book presents a narrative focused on the experiences of the Scottish Highlanders during the Peninsular War, intertwining historical events with fictional tales. The story prominently follows Ronald Stuart, a young Highlander who, in the midst of familial feuds and romantic tensions, embarks on a military adventure as he pursues honor and love. At the start of the novel, we are introduced to the longstanding rivalry between two Highland clans, the Lisles and the Stuarts, against a backdrop of the serene yet rugged Scottish landscape. The narrative highlights characters like Sir Allan Lisle and Ronald Stuart, exploring their personal conflicts and deep-seated emotions as Ronald prepares to leave for military service, battling against the enmity of their families. Ronald$1 (Bs bond with Alice Lisle, intertwined with the historical context of Highland loyalties and aspirations, adds a romantic element that complicates his military ambitions. The opening chapters set the stage for a rich blend of action, drama, and heartfelt relationships against the tumultuous events of war. (This is an automatically generated summary.)s
Release date is 2017-06-15
Produced by Al Haines
Keywords: Peninsular War, 1807-1814 -- Fiction; Great Britain. Army. Gordon Highlanders -- Fiction